Planning Your Time in Retirement: How to Cultivate a Leisure Lifestyle to Suit Your Needs and Interests - Stebbins, Robert A. (Rowman & Littlefield Publishers, 2013)
Much of what is written about getting old has a negative feel to it, which is certainly not entirely unjustified. Health may begin to fail. Finances may become tighter as income dwindles or stops altogether. Family and friends may move away or move on. But the retirement years do not have to be negative or bleak. Within this “dark scenario,” a positive existence is possible. Planning Your Time in Retirement focuses on the variety of free-time activities available to retirees as related to their physical, social, and economic situation in old age, helping readers find out what their passions are, what the possibilities might be, and how to cultivate their own leisure lifestyle. For some retirees, a post-work existence consisting of fun works well, for they have managed to shape an interesting casual leisure lifestyle based on easygoing activities that make them happy. Seldom included in the popular image of leisure, however, are other types of leisure that are also widely available to retirees. Regardless of means, the retirement years can consist of activities and pastimes that fulfill the interests and pursuits of any retiree. A variety of exciting leisure activities exists, which retirees may pursue within their financial, physical, mental, and geographic limits. This book provides a guide—the serious leisure perspective—for exploring these activities and choosing those that fit one’s tastes, aptitudes, and abilities. At its most appealing, a leisure lifestyle includes a balance of easy-to-do casual interests as well as serious ones that require knowledge, effort, and perseverance. For some, enjoyment and fulfillment may come from engaging in volunteer work, while for others it may involve leisure activities from which they gain some form of payment. By employing the notion of positive simplicity—simple living in the domain of leisure—many people at this stage of life can delight in these final years. While time and money cannot be ignored, finding those activities that allow for engagement, reward, and simplicity can result in days, even years, of leisure that is meaningful, enjoyable, healthy, and empowering.